A new genus and two new species of Apomecynini, a new species of Desmiphorini, and new records in Lamiinae and Disteniidae (Coleoptera) - Heffern, Daniel; Santos-Silva, Antonio; Botero, Juan Pablo (Zootaxa, 2019)
A new Mexican state record is provided for Holoaerenica apleta Galileo & Martins, 1987 and a new Honduran record is provided for Antodice sexnotata Franz, 1959 (both Aerenicini). A new Mexican state record is provided for Ptericoptus caudalis Bates, 1880 (Apomecynini). A new record for Panama is provided for Novantinoe hovorei Santos-Silva, 2007 (Disteniidae, Disteniinae). Vandenbergheius celaquensis, gen. nov., sp. nov. (Apomecynini) is described from Honduras; Adetus croton (Apomecynini) is described from the USA (Texas), Mexico (Sonora, Jalisco, Chiapas, Michoacán, Quintana Roo, Tamaulipas, Yucatán, Nuevo León), and Honduras; and Estoloides sinaloana (Desmiphorini) is described from Mexico (Sinaloa).